Supervision of Drinking Water Quality in North Sumatra Province - Yulia Khairina Ashar; Indah Syafitri Nasution; Rosalinda Harahap; Najah Ulfa Ridho; Winta Oktavia Berutu (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Water is the most important element in life after air, but water is also the main cause of many diseases. This study uses a descriptive quantitative method with the Secondary Data Analysis approach. We got this secondary data from the Environmental Health Inspection of the North Sumatra Provincial Health Office results. The research results from these data are data Drinking Water Quality Monitoring data in 2021-2022 with 1,317 facilities owned by North Sumatra Province in 33 Regencies/Cities. To data for North Sumatra Province in 2021, 74.39% of the 1,316 facilities will carry out Drinking Water Quality Monitoring. Moreover, it has reached the target indicator of 65%. Meanwhile, Gunung Sitoli City needs communal drinking water facilities. Data for the Province of North Sumatra for 2022, the achievement of the indicator for supervised drinking water facilities is 68.03%, meaning that it still has yet to reach the target of 70%. In conclusion, monitoring of drinking water quality in Sumatra province has been carried out but has yet to meet the desired standards. There are still many areas where supervision of the facilities has yet to be carried out. Most often occurs because the area still needs sanitary staff to supervise. Many human resources still deal with this problem but must understand how the supervision procedures should be. Suggestions for the government in the future are to conduct the government carries out Drinking Water Quality Monitoring carried out once regularly according to a schedule per month or every six months to check the quality of drinking water, including inspection of physical, biological, and chemical parameters.Keywords: Drinking Water, Inspection, Monitoring, Water quality